2013
DOI: 10.7555/jbr.27.20110142
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of lysyl oxidase-like 1 and fibulin-5 in the cardinal ligament tissue of patients with pelvic floor dysfunction

Abstract: Pelvic organ prolapse (POP) is a disabling disorder in women characterized by a loss of pelvic floor support, leading to the herniation of the uterus into or through the vagina. POP is a complex problem that likely involves multiple mechanisms with limited therapies available, and is associated with defects in connective tissue including elastic fibers. This study was designed to investigate the expression of fibulin-5 and lysyl oxidase-like 1 (LOXL1) in the cardinal ligament in samples taken from the POP grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In a different study, a role for LOXL1 in elastic fiber renewal in adult tissues was proposed, based on high incidence of pelvic organ prolapse (POP) and permanent damage to the pelvic floor in post partum LOXL1-null mice (110). Subsequent studies of human populations have produced conflicting data regarding the role of LOXL1 in POP: one group has reported an increase in LOXL1 mRNA and protein in the uterosacral ligaments of patients with POP (111), while others report that expression of LOXL1 mRNA (89,112,113) and protein (114,115) are significantly down-regulated in the pelvic connective tissues of POP patients. While the majority of the data support the hypothesis that LOXL1 plays a critical role in elastin maturation, additional investigation is needed to resolve this discrepancy.…”
Section: Lysyl Oxidase Familymentioning
confidence: 99%
“…In a different study, a role for LOXL1 in elastic fiber renewal in adult tissues was proposed, based on high incidence of pelvic organ prolapse (POP) and permanent damage to the pelvic floor in post partum LOXL1-null mice (110). Subsequent studies of human populations have produced conflicting data regarding the role of LOXL1 in POP: one group has reported an increase in LOXL1 mRNA and protein in the uterosacral ligaments of patients with POP (111), while others report that expression of LOXL1 mRNA (89,112,113) and protein (114,115) are significantly down-regulated in the pelvic connective tissues of POP patients. While the majority of the data support the hypothesis that LOXL1 plays a critical role in elastin maturation, additional investigation is needed to resolve this discrepancy.…”
Section: Lysyl Oxidase Familymentioning
confidence: 99%
“…Elastin helps tissues to stretch and return to their original shape without energy input, which is extremely important in the regenerative system. Many studies have shown that elastin metabolism is affected in PFD because of increased degradation, abnormal synthesis, and interruption in elastin homeostasis [ 17 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It functions to facilitate the stretch and return of tissues to their original form in the absence of energy. Metabolism of elastin has been shown to be affected in PFD as a result of abnormal synthesis, interruption in homeostasis, as well as increased degradation [1922]. Weakened connective tissues in the pelvis are thought to contribute to pathophysiological development of PFD.…”
Section: Discussionmentioning
confidence: 99%